UniPR1331, a small molecule targeting Eph/ephrin interaction, prolongs survival in glioblastoma and potentiates the effect of antiangiogenic therapy in mice - Festuccia, Claudio (Oncotarget, 2018)
Glioblastoma multiforme (GBM) is the most malignant brain tumor, showing high resistance to standard therapeutic approaches that combine surgery, radiotherapy, and chemotherapy. As opposed to healthy tissues, EphA2 has been found highly expressed in specimens of glioblastoma, and increased expression of EphA2 has been shown to correlate with poor survival rates. Accordingly, agents blocking Eph receptor activity could represent a new therapeutic approach. Herein, we demonstrate that UniPR1331, a pan Eph receptor antagonist, possesses significant in vivo anti-angiogenic and anti-vasculogenic properties which lead to a significant anti-tumor activity in xenograft and orthotopic models of GBM. UniPR1331 halved the final volume of tumors when tested in xenografts (p<0.01) and enhanced the disease-free survival of treated animals in the orthotopic models of GBM both by using U87MG cells (40 vs 24 days of control, p<0.05) or TPC8 cells (52 vs 16 days, p<0.01). Further, the association of UniPR1331 with the anti-VEGF antibody Bevacizumab significantly increased the efficacy of both monotherapies in all tested models. Overall, our data promote UniPR1331 as a novel tool for tackling GBM.